On the Optimal Design of Place-Based Policies: A Structural Evaluation of EU Regional Transfers - Yashar Blouri; Maximilian von Ehrlich (Center for Economic Studies and ifo Institute (CESifo), 2017)
We quantify general equilibrium effects of place-based policies in a multi-region framework with mobility, trade and agglomeration economies. Using detailed data on EU transfers, we infer the local effects of different transfer types on productivity, income and transportation cost. Based on these estimates and the general equilibrium model we derive the spatial distribution of economic activity and the resulting aggregate welfare effects if (i) no transfers were paid and taxes set to zero, (ii) transfers were distributed uniformly, (iii) transfers were welfare-optimally distributed. Characterizing the optimal distributions, we reveal complementarities between transfer types and between transfers and local endowments.
Keywords: R10; R50; F10; F20; H20; 330; economic geography; place-based policies; structural estimation subsidies; public investments; European structural funds